The Influence of Brand Image, Product Quality, And Price on Purchase Intention for Skintific Products - Diana Nurfita; Basuki, Ananto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to determine the influence of brand image, product quality, and price on the purchase intention of Skintific products. This is an explanatory research study that explains the causal relationship between variables through hypothesis testing. A sample of 84 respondents was obtained using a non-probability sampling technique with a purposive sampling method. The data used were primary data collected from questionnaires using a five-point Likert Scale. The analysis tool used was the Statistical Package for the Social Sciences (SPSS) to perform validity, reliability, classical assumption, and multiple linear regression tests. The findings of the study show that brand image, product quality, and price each have a positive and significant effect on purchase intention. Furthermore, brand image, product quality, and price simultaneously have a significant effect on purchase intention. This research suggests that the Skintific brand should make brand image, product quality, and price its main strategy in an effort to attract consumer purchase intention and win the competition.